Management of a Rare Complication of Epidural Analgesia in an Obese Laterally Positioned Parturient: Catheter Entrapment Next to the Inferior Vena Cava. Issue 3 (September 2016) - Amir, A.; Lash, V.; Moore, A.; Rao, P.; Torres, C.; Kaufman, I.
Abstract : ( Reg Anesth Pain Med. 2015;40(6):726–728) Although epidural analgesia is an excellent choice for labor, catheters are usually placed without visual confirmation and can be misplaced. Common locations for misplaced epidural catheters include intravascular, subdural, and intrathecal. However, it is possible for them to be misplaced into the retroperitoneum, leading to potentially disastrous results. This paper reports the case of an obese patient who presented with an epidural catheter embedded next to her inferior vena cava.